Enhancing School Promotion Effectiveness through 2D Animation Training: A Community Service Project at SMK-NU Donomulyo - Vivi Aida Fitria; Nicholaus Wayong Kabelen; Lilis Widayanti; Lukman Hakim (Institut Teknologi dan Bisnis Asia Malang, 2026)
Purpose: This study aims to enhance SMK-NU Donomulyo's digital promotion capacity through 2D animation training, addressing the school's limited resources for producing effective promotional content in the competitive educational landscape. Method: A participatory action research design was employed, engaging teachers and Visual Communication Design students in hands-on training using Figma for graphic design, complemented by Canva and Animaker for animation development. Practical Applications: The findings enable sustainable, independent creation of promotional content, strengthening the school's digital marketing capabilities and enhancing visibility across social media platforms such as Instagram, TikTok, and YouTube. Conclusion: With 96% of participants mastering animation fundamentals and 100% successfully producing promotional animations, this training demonstrates that accessible, cost-effective tools can effectively build institutional digital capacity for educational promotion in the digital era.